2022
DOI: 10.1029/2021jd036242
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Warm Freezing Rain: Observation and Modeling Study

Abstract: Freezing rain has been normally considered to be composed of supercooled raindrops when the 2 m air temperature (hereafter Tas ${T}_{as}$) is below freezing. However, according to a statistical survey of freezing rain observations in China from 2000 to 2019, we find that there were 656 events that occurred at Tas ${T}_{as}$ greater than 0°C (hereafter warm freezing rain and denoted by WFR), which account for 7% of the total freezing rain observations. Additionally, nearly 3% (266 observations) of freezing rain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although it has been shown in glacier‐covered watersheds, the mean elevation of the watershed is a factor that decreases water temperature (Fellman et al 2014), a similar trend was observed in the analysis for the Japanese archipelago, where glaciers are virtually non‐existent. This may depend on higher elevations with lower temperatures and rainfall temperatures (Lu et al 2022). Another important finding is that the relief amount in the watershed also affects the water temperature in river estuaries at a distance from the headwaters.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown in glacier‐covered watersheds, the mean elevation of the watershed is a factor that decreases water temperature (Fellman et al 2014), a similar trend was observed in the analysis for the Japanese archipelago, where glaciers are virtually non‐existent. This may depend on higher elevations with lower temperatures and rainfall temperatures (Lu et al 2022). Another important finding is that the relief amount in the watershed also affects the water temperature in river estuaries at a distance from the headwaters.…”
Section: Discussionmentioning
confidence: 99%
“…As high-voltage transmission lines are usually erected in high-altitude mountainous areas, they are highly vulnerable to freezing rain (FR) and supercooled fog (SF); the cooling droplets condensed on the cable or snow slush frozen on the cable will cause ice coating on cable, which is usually called as "wire icing". Wire icing will not only affect the normal operation of the transmission network but also cause serious insulator flashover, cable breaking after galloping, damage to the fittings and insulators, tilt and collapse of poles towers, and other accidents (Adhikari and Liu, 2019;Deng et al, 2012;Lu et al, 2022). Since the deployment of China's 330 and 500 kV highvoltage transmission lines, wire icing disasters have increased and seriously affected the safe and stable operation of the power grid (Wang and Jiang, 2012;Hu et al, 2016;Huang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%